EFFECT OF CUPPING THERAPY TO TOTAL CHOLESTEROL LEVEL TO HYPERCHOLESTEROLEMIA - Evania Zuhriyah Aulfah Arozi; Burhanto; wibowo, thomas ari (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Hypercholesterolemia is a condition in which cholesterol concentrations in the blood exceed normal levels, resulting in death if total cholesterol levels exceed 240 mg/dl. The purpose of this study was to determine the effect of cupping therapy on total cholesterol levels in hypercholesterolemia patients at the Islamic Medication Clinic of Reflection and Cupping Samarinda. This was a quantitative study with The pre-experimental group was combined with the pre-test and post-test groups. The total number of participants in this study was 20, and their total cholesterol levels were measured before and after they were cupped. The Shapiro-Wilk test was used to determine normalcy. Paired T-Test was used in bivariate analysis. The results of the bivariate analysis using the T-test revealed that there was a significant effect of cupping therapy on total cholesterol levels in hypercholesterolemia patients, with a p value of 0.00 < 0.05. According to the results of the variable analysis, there was an effect of cupping therapy on total cholesterol levels and hypercholesterolemia. According to the findings of the study, cupping therapy should be one of the therapies used to control total cholesterol levels, and it is hoped that other researchers will conduct additional research on cupping therapy. Cooperate with the laboratory so that total cholesterol, LDL, HDL, and triglyceride levels can be determined. This cupping research could also be expanded to include its benefits for other medications.